2021
DOI: 10.3389/fpsyt.2020.598720
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Well-Being of Frontline Physicians Working in Civil Wars Under Coronavirus Disease 2019 Pandemic Conditions

Abstract: Background and Objective: Emergency medical physicians are regarded as essential frontline staff in combating the coronavirus disease 2019 (COVID-19) pandemic. These health-care workers are faced with significant stressors in addition to the usual stress felt in their regular work. Therefore, this study aimed to examine the prevalence of anxiety, depression, and burnout among emergency physicians on the frontline of the COVID-19 pandemic.Method: Using a cross-sectional study methodology, we surveyed physicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 60 publications
4
24
0
1
Order By: Relevance
“…Our results are comparable to some similar studies in the literature published since the beginning of the pandemic (11,57,(62)(63)(64)(65)(66)(67)(68)(69)(70). Indeed, among the studies with a similar design as ours, e.g., a cross-sectional study with the aim of verifying factors associated with per-pandemic psychological distress (burnout, psychopathologies) in healthcare workers, the rates of distress and the factors reported are similar to what we present here.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are comparable to some similar studies in the literature published since the beginning of the pandemic (11,57,(62)(63)(64)(65)(66)(67)(68)(69)(70). Indeed, among the studies with a similar design as ours, e.g., a cross-sectional study with the aim of verifying factors associated with per-pandemic psychological distress (burnout, psychopathologies) in healthcare workers, the rates of distress and the factors reported are similar to what we present here.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, several studies have shown high rates of burnout (64,66,67,69,70), which are comparable to the 51.8% reported here. However, the factors associated with the development of burnout sometimes differ from the ones we found, with reports of workload, type of employment and participation in training programs, all of which were not found to be significant in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Studies have highlighted the presence of BOS in workers struggling with COVID-19 patients. HCWs include frontline nurses in emergency departments [47] and ICUs [48], Libyan [49] or Indian [50] physicians, Spanish nurses [51], Japanese radiological technologists and pharmacists [52], and others. A state of persistent burnout, that influenced sleep quality, was observed in a longitudinal study on a small group of HCWs [53].…”
Section: Discussionmentioning
confidence: 99%
“…After working experiences at frontline of COVID-10 pandemic, about 24.7–50.4%, 19.8–44.6%, and 21.9–71.5% of healthcare professionals in China or Italy reported depressive mood, anxiety, and perceived distress, which were higher prevalence compared to those at baseline (=prior to the working experiences at frontline of COVID-19 pandemic) [ 41 44 ]. In addition, lowered self-efficacy at work (or a lower sense of personal accomplishment) was also reported from 21.4–22.7% of healthcare professionals of Libya during COVID-19 pandemic [ 45 , 46 ]. For the cases of MERS outbreak, 26.6% of doctors who dealt with the MERS outbreak in South Korea [ 38 ] and 27.5% of doctors responding to the SARS outbreak in Taiwan exhibited depression [ 47 ].…”
Section: Discussionmentioning
confidence: 99%